THE EFFECT OF ADOLECENTS ON FAMİLY CONSUMİNG BEHAVİOURS (Third Sector Social Economic Review, 2010)
This study has been done for the purpose of determining the effect of adolescents on family consuming behaviors. Totally, 300 hundred students whoseages range from 11 to 18 and who were willing to participate in the study and were attending primary and high schools in the center of Ankara were included in the sampling of the research. The study has been done in the scanning model and the questionnaire form has been used as the study instrument. The collected data has been evaluated through the x2 analysis by presenting in cross tables. It has been discovered that adolescents have considerable effect on the categories of sporting equipment, recreation/free time activities, writing materials (stationary materials), cassettes, CDs, games, toys and individual care products which are from their purchasing areas. In terms of family consuming areas it is assessed that the adolescents are effective in recreation/free time activities category, only after the common decision of the family. Among the purchasing categories, adolescents are the most effective in selecting the blend. Generally, it is observed that when the adolescents get older and the income of the family rises, they communicate their opinions more on family purchasing decisions. When the price of the product is high, fathers are more effective with decisions and mothers’ effectiveness with decisions rise when their economical power rises. In the direction of the collected data, it is suggested to the parents to guide the adolescents in evaluating the quality, price and blend of the product or services that they will use, but let them have the last decision, and allow them to discuss on family decisions.
Keywords: Consumption; consuming behaviors; purchasing decisions; adolescent; family